Genome-wide identification and expression profiling of Alba gene family members in response to abiotic stress in tomato (Solanum lycopersicum L.) - Antt Htet Wai (BMC, 2021)
Abstract Background Alba (Acetylation lowers binding affinity) proteins are an ancient family of nucleic acid-binding proteins that function in gene regulation, RNA metabolism, mRNA translatability, developmental processes, and stress adaptation. However, comprehensive bioinformatics analysis on the Alba gene family of Solanum lycopersicum has not been reported previously. Results In the present study, we undertook the first comprehensive genome-wide characterization of the Alba gene family in tomato (Solanum lycopersicum L.). We identified eight tomato Alba genes, which were classified into two groups: genes containing a single Alba domain and genes with a generic Alba domain and RGG/RG repeat motifs. Cis-regulatory elements and target sites for miRNAs, which function in plant development and stress responses, were prevalent in SlAlba genes. To explore the structure-function relationships of tomato Alba proteins, we predicted their 3D structures, highlighting their likely interactions with several putative ligands. Confocal microscopy revealed that SlAlba–GFP fusion proteins were localized to the nucleus and cytoplasm, consistent with putative roles in various signalling cascades. Expression profiling revealed the differential expression patterns of most SlAlba genes across diverse organs. SlAlba1 and SlAlba2 were predominantly expressed in flowers, whereas SlAlba5 expression peaked in 1 cm-diameter fruits. The SlAlba genes were differentially expressed (up- or downregulated) in response to different abiotic stresses. All but one of these genes were induced by abscisic acid treatment, pointing to their possible regulatory roles in stress tolerance via an abscisic acid-dependent pathway. Furthermore, co-expression of SlAlba genes with multiple genes related to several metabolic pathways spotlighted their crucial roles in various biological processes and signalling. Conclusions Our characterization of SlAlba genes should facilitate the discovery of additional genes associated with organ and fruit development as well as abiotic stress adaptation in tomato.